Galcanezumab in Patients with Multiple Previous Migraine Preventive Medication Category Failures: Results from the Open-Label Period of the CONQUER Trial - Reuter, Uwe; Lucas, Christian; Dolezil, David; Hand, Austin L.; Port, Martha D.; Nichols, Russell M.; Stroud, Chad; Tockhorn-Heidenreich, Antje; Detke, Holland C. (Advances in therapy, 2021)
Introduction Results from the open-label extension of the phase 3b CONQUER trial are presented to evaluate the effectiveness and safety of galcanezumab, a monoclonal antibody targeting calcitonin gene-related peptide, for up to 6 months in patients with multiple prior migraine preventive treatment failures. Methods Patients were 18–75 years old with episodic or chronic migraine and 2–4 standard-of-care migraine preventive medication category failures. After 3 months of randomized treatment with galcanezumab (120 mg/month with 240 mg loading dose; n = 232) or placebo ( n = 230), patients entered a 3-month open-label extension (120 mg/month galcanezumab with a blinded 240 mg loading dose for previous-placebo patients). Primary efficacy measure was mean change from double-blind baseline in monthly migraine headache days. Results A total of 432/449 patients (96%) who entered open-label treatment completed the study. Mean change in monthly migraine headache days in the total population, which was − 1.3 for placebo and − 4.4 for galcanezumab patients at the end of double-blind treatment ( p < 0.001), was − 5.2 and − 5.6, respectively, at the end of open-label treatment with galcanezumab. Among patients with episodic migraine, mean change in monthly migraine headache days had been − 0.6 for placebo and − 2.8 for galcanezumab after double-blind treatment ( p < 0.001) and was − 4.5 and − 3.8, respectively, after open-label treatment. Among patients with chronic migraine, mean change in monthly migraine headache days had been − 2.5 for placebo and − 6.6 for galcanezumab after double-blind treatment ( p < 0.001) and was − 6.5 and − 8.2, respectively, after open-label treatment. Adverse events were similar to those observed during double-blind placebo treatment. Review of data in elderly patients (65–75 years of age) indicated that galcanezumab was well tolerated in this age group, with no safety issues identified. Conclusions Galcanezumab was effective and safe during open-label treatment in patients who had experienced failures of previous migraine preventives. Clinical Trial Registration ClinicalTrials.gov identifier NCT03559257.